The Role of Teacher Behavior as a Mediator in the Relationship Between Social Support and Students’ School Well-Being at University X - Mailani, Indah; Sahrani, Riana; Satyadi, Heryanti (GoAcademica Research & Publishing, 2025)
This study examined the mediating role of teacher behavior in the relationship between parental and peer social support and students’ school well-being. Conducted as a case study at University X, the research aimed to understand how teacher behavior influences students’ academic well-being within the context of changing educational environments. Using a quantitative correlational design, data were collected from 305 active students aged over 18 through purposive sampling. Standardized questionnaires were used to measure teacher behavior, school well-being, and social support from parents and peers. The data were analyzed using path analysis with JASP and SPSS software. Results indicated that parental and peer social support significantly influenced students’ school well-being. Furthermore, teacher behavior was found to partially mediate this relationship, suggesting that supportive and consistent lecturer conduct enhances the positive impact of social support on academic well-being. These findings highlighted the importance of teacher behavior as an educational resource and offered valuable insights for improving student well-being, particularly in higher education settings experiencing transitions in learning modalities.